2022
DOI: 10.1007/s00167-022-07053-9
|View full text |Cite
|
Sign up to set email alerts
|

Higher preoperative expectations predict better outcomes in shoulder surgery patients

Abstract: Purpose The purpose of this study is to determine if preoperative expectations (PE) are an independent predictor of greater 2-year outcomes and greater improvement from baseline in shoulder surgery patients. Methods Two-hundred and sixteen patients who underwent shoulder surgery at one institution were studied. Patients completed both preoperative and 2-year follow-up questionnaires including PROMIS (Patient-Reported Outcome Measurement Information System) computer-adaptive testing in six domains, American Sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…They demonstrated that patients’ expectations towards the outcome of surgery are dependent on diagnosis, demographics and functional status and developed a template for surgeons to discuss realistic and unrealistic goals with the patient and consequently improve shared decision making [ 11 ]. Kaveeshwar et al interviewed 216 patients who underwent shoulder surgery, showing that greater expectations are predictive for better outcome scores with reference to pain relief, shoulder function and social satisfaction [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that patients’ expectations towards the outcome of surgery are dependent on diagnosis, demographics and functional status and developed a template for surgeons to discuss realistic and unrealistic goals with the patient and consequently improve shared decision making [ 11 ]. Kaveeshwar et al interviewed 216 patients who underwent shoulder surgery, showing that greater expectations are predictive for better outcome scores with reference to pain relief, shoulder function and social satisfaction [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that higher degrees of pain, reduced function in performing ADL, and lower expectations were important contributing factors to being ready for surgery. Role of preoperative expectations in final outcomes have been extensively examined 13,[50][51][52] and achievable expectations for joint replacement surgery are associated with better overall satisfaction. The evidence suggests that patients tend to overestimate the potential benefit of surgery and underestimate the potential for complications.…”
Section: Discussionmentioning
confidence: 99%
“…Also a variety of mental factors, such as anxiety ( 13 ), depression ( 13 ), pain catastrophizing ( 14 ), personality (e.g. emotional stability/neuroticism) ( 15 , 16 , 17 ), coping mechanisms ( 18 , 19 , 20 ), resilience ( 21 ), expectations ( 22 , 23 , 24 ), self-efficacy ( 25 ), and illness perceptions ( 26 ), are mentioned to influence symptoms before and after surgery. Since these factors can overlap, coincide, oppose, or enhance each other, we choose the most mentioned in the literature to discuss in this paper and we do not claim to be complete in reviewing the existing literature.…”
Section: Psychological Factorsmentioning
confidence: 99%